1964
DOI: 10.1152/ajplegacy.1964.206.6.1309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total adrenalectomy on gastric secretion in chronic gastric fistula rats

Abstract: Basal gastric secretion of rats with chronic fistulas was studied before and after adrenalectomy or sham operation. A marked exponential fall in concentration and output of free and total acid resulted in virtual anacidity within 3–7 weeks following adrenalectomy. Failure in parietal cell secretion was not accompanied by significant decrease in parietal cell mass. Pepsin concentration and output as well as volume also fell exponentially but more gradually. No significant change in total chloride concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
1
1

Year Published

1966
1966
1981
1981

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
3
5
1
1
Order By: Relevance
“…3) and confirmed results obtained in a previous study (Cooke et al, 1966a). Various mechanisms have been postulated to explain the reduction in acid output; neither parietal cell atrophy (Baker and Bridgman, 1954;Bralow, Komarov and Shay, 1964) nor metabolic alterations (Ramey and Goldstein, 1957) nor changes in the mucosal barrier (Cooke et al, 1966a) have been demonstrated. In contrast to the decrease in acid output following adrenalectomy using histamine stimulation, acid output was unchanged when gastrin was used as a stimulus (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…3) and confirmed results obtained in a previous study (Cooke et al, 1966a). Various mechanisms have been postulated to explain the reduction in acid output; neither parietal cell atrophy (Baker and Bridgman, 1954;Bralow, Komarov and Shay, 1964) nor metabolic alterations (Ramey and Goldstein, 1957) nor changes in the mucosal barrier (Cooke et al, 1966a) have been demonstrated. In contrast to the decrease in acid output following adrenalectomy using histamine stimulation, acid output was unchanged when gastrin was used as a stimulus (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…3). The difference between the findings of the present investigation and those reported using the rat (Tuerkischer and Wertheimer, 1945;Bralow et al, 1964) may be resolved on a basis of species difference. In the rat, chief cell involution was reported to occur after bilateral adrenalectomy (Abrams and Baker, 1954) but this was not found in the dog many months after hypophysectomy (Jacobson and Magnani, 1964).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Such a short-term effect of corticosteroids on the acidification of gastric content seems more compatible with a stimulation of Hf generation processes in already differentiated parietal cells than with a corticosteroid-induced architectural matbration of the mucosa. In the adult, it is generally recognized that corticosteroids are necessary for the maintenance of normal gastric acid secretion; adrenalectomy leads to a marked fall in acid concentration of the gastric juice (3). However, results concerning the effect of corticosteroid treatment are conflicting; some authors have observed an increased acid secretion whereas others fail to obtain any evidence of a rise in the gastric acid secretion (6).…”
Section: Discussionmentioning
confidence: 99%
“…This paper reports the results of three experiments in rats in which the effects of hypophysectomy on the growth of the gastric mucosa were determined from the changes observed in the weight of the stomach, the surface area, height and volume of the fundic mucosa, and the total parietal cell population of the stomach; a preliminary account of some of the results obtained has been given elsewhere (Crean, 1961;1963b). ESTIMATION the surface area and volume of the gastric mucosa were estimated according to the methods described originally by Cox and Barnes (1945) as modified by Card and Marks (1960); substantially the same methods have been used to estimate the parietal cell population of the whole or resected human stomach (Cox, 1952;Card and Marks, 1960) and of the whole stomach of the dog, guinea-pig, and rat (Marks, Komarov, and Shay, 1960;Reid, Hackett, and Welbourn, 1961;Cox and Barnes, 1945;Marks, 1957;Bralow and Komarov, 1962;Bralow, Komarov, and Shay, 1964).…”
mentioning
confidence: 99%